ANDRAGOGY: TEORI PEMBELAJARAN AGAMA ISLAM PADA USIA DEWASA - Nurul Aini (Edu Global : Jurnal Pendidikan Islam, 2021)
The aim of this research is know how to deepen the knowledge of Islam by using the theory of Andragogy. This study uses a qualitative method in the literature research section. Sources of data are taken from various printed and electronic texts and discourses that are considered relevant, such as books and journals. The approach uses an interpretive approach. The benefit of this research is that people who have entered adulthood do not feel ashamed and hesitate to continue learning, because learning does not look at age. Based on the research, it is known that andragogy learning theory has an important role in studying Islamic education. This is because there are many Islamic laws that make the object of the perpetrator as a mukallaf (adult). Andragogy learning success requires good manners, interests and motivation. Various methods can be used in the learning process, namely the lecture method, discussion, demonstration to practical training. The stages in the andragogy learning process start from preparation for a good climate, formulating goals, determining relevant materials and methods.